Nursing's social policy statement : the essence of the profession - American Nurses Association (Silver Spring, Md. : American Nurses Association, 2010)
"Last revised in 2003, this comprehensive revision to an enduring text updates its framework on the social roots and relationships of the nursing profession and nursing practice. An integrated discussion of its organizing topics - the social context of nursing, nursing's social contract, the definition of nursing, nursing's knowledge base, the scope of nursing practice, the standards of nursing practice, and the regulation of nursing - delineates the essential elements of the profession for nurses in any level or setting of practice and education."--Publisher's description.
Nursing's social policy statement: an overview -- Social context of nursing : The social concerns in health care and nursing ; The authority for practice for nurses ; The elements of nursing's social contract ; Professional collaboration in health care -- Definition of nursing : Human responses ; Theory application ; Nursing actions ; Outcomes -- Knowledge base for nursing practice -- Scope of nursing practice : Specialization in nursing practice ; Advanced nursing practice ; Advanced practice registered nurses (APRNs) ; Additional specialized advanced nursing roles -- Standards of professional nursing practice : Definition and function of standards ; Development of standards ; Standards of professional nursing practice ; Standards of practice ; Standards of professional performance ; Application of scope and standards ; Code of ethics for nurses ; Autonomy and competent practice -- Regulation of professional nursing : Professional regulation ; Legal regulation ; Institutional policies and procedures ; Self-regulation -- Application of nursing's social policy statement -- Appendices : A. Consensus Model for APRN Regulation: Licensure, Accreditation, Certification, and Education (2008) -- B. Nursing's Social Policy Statement, 2nd Edition (2003) -- C. Nursing's Social Policy Statement (1995) -- D. Nursing: A Social Policy Statement (1980) -- E. The development of foundational nursing documents and professional nursing: a timeline.
Includes bibliographical references and index.
Keywords: Nursing; Nursing -- Philosophy; Nursing -- Practice; Nursing -- Social aspects; Philosophy, Nursing -- Guideline; Nurse's Role -- Guideline; Nursing -- standards -- Guideline; Social Responsibility -- Guideline